Synthesis and Spectroscopic Characterization for Some Metal ion Complexes with 2-Hydroxy-3-((5-Mercapto-1,3,4-Thiadiazol-2-yl)Diazenyl)-1-Naphthaldehyde (Baghdad Science Journal, 2016)
New metal ion complexes were synthesized with the general formula; K[PtLCl4], [ReLCl4] and K[ML(Cl)2] where M = Pd(II), Cd(II), Zn(II) and Hg(II), from the Azo ligand (HL) [2-Hydroxy-3-((5-mercapto-1,3,4-thiadiazol-2-yl)diazenyl)-1-naphth aldehyde] (HL) the ligand was synthesized from (2-hydroxy-1-naphthaldehyde) and (5-amino-1,3,4-thiadiazole-2-thiol). The ligand and its metal complexes are characterized by phisco- chemical spectroscopic techniques (FT.IR, UV-Vis and Mass spectra, elemental analysis, molar conductivity, Atomic Absorption, Chloride contain and magnetic susceptibility). The spectral data suggest that the (HL) behaves as a bidentate ligand in all complexes. These studies revealed tetrahedral geometries for all metal complexes, except square planar for Pd(II) complex and except octahedral geometry for Pt(IV) and Re(V) complexes. The study of complexes formation via molar ratio of (M:L) as (1:1). Theoretical treatment of this ligand and its metal complexes in gas phase using Hyper chem.8 was preformed.